Use of biological meshes for abdominal wall reconstruction in highly contaminated fields - Cavallaro, Andrea (Baishideng, 2010)
Abdominal wall defects and incisional hernias represent a challenging problem. In particular, when a synthetic mesh is applied to contaminated wounds, its removal is required in 50%-90% of cases. Biosynthetic meshes are the newest tool available to surgeons and they could have a role in ventral hernia repair in a potentially contaminated field. We describe the use of a sheet of bovine pericardium graft in the reconstruction of abdominal wall defect in two patients. Bovine pericardium graft was placed in the retrorectus space and secured to the anterior abdominal wall using polypropylene sutures in a tension-free manner. We experienced no evidence of recurrence at 4 and 5 years follow-up.